High-energy emission as signature of magnetic field amplification in neutron star mergers - Fraija Cabrera, Nissim Illich (2015)
The merger of a binary neutron star system is suggested as the central engine of short gamma-ray bursts (sGRBs). For the merger process, simulations predict that magnetic field is amplified beyond magnetar field strength by Kelvin-Helmholtz instabilities. With the Large Area Telescope (LAT), bursts have been detected that show a temporally extended component in coincidence with a short-lasting peak at the end of the prompt phase. We show that the presence of these LAT components in a sGRB could provide evidence of magnetic field amplification in the neutron star merger.